Targeting Paretic Propulsion and Walking Speed With a Soft Robotic Exosuit: A Consideration-of-Concept Trial - Porciuncula, Franchino; Baker, Teresa C.; Arumukhom Revi, Dheepak; Bae, Jaehyun; Sloutsky, Regina; Ellis, Terry D.; Walsh, Conor J.; Awad, Louis N. (Frontiers in Neurorobotics, 2021)
Soft robotic exosuits can facilitate immediate increases in short- and long-distance walking speeds. We sought to assess the feasibility and rehabilitative potential of applying propulsion-augmenting exosuits as part of an individualized and progressive training program to retrain faster walking and the underlying propulsive strategy. A 54-yr old male with chronic hemiparesis completed 5 daily sessions of Robotic Exosuit Augmented Locomotion (REAL) gait training. Repeated baseline assessments of comfortable walking speed over a 2-year period provided a stable baseline from which the effects of REAL training could be elucidated. REAL training consists of high-intensity, task-specific, and progressively challenging walking practice augmented by a soft robotic exosuit and is designed to facilitate faster walking by way of increased paretic propulsion. Additional outcomes included paretic propulsion, maximum walking speed, and 6-minute walk test distance. Comfortable walking speed was stable at 0.96 m/s prior to training and increased by 0.30 m/s after training. Clinically meaningful increases in maximum walking speed (∆: 0.30 m/s) and 6-minute walk test distance (∆: 59 m) were similarly observed. Improvements in paretic peak propulsion (∆: 2.80 %BW), propulsive power (∆: 0.41 W/kg), and trailing limb angle (∆: 6.2 degrees) were observed at comfortable walking speed (p's < 0.05). Likewise, improvements in paretic peak propulsion (∆: 4.63 %BW) and trailing limb angle (∆: 4.30 degrees) were observed at maximum walking speed (p's < 0.05). The REAL training program is feasible to implement after stroke and capable of facilitating rapid and meaningful improvements in paretic propulsion, walking speed, and walking distance.